Formação de professores de língua inglesa em um curso de letras com habilitação única em inglês - Rodrigues, Beatriz Gama (2007)
This study aims at describing and interpreting the phenomenon of English teachers education in a Language graduation course, from the point of view of those who lived this experience: the students, who were developing teachers, and the teacher-researcher. This research was started with the history of English as a foreign language teaching in Brazil and of the Language graduation course of the university where the phenomenon was observed. This study was grounded on education of critical-reflexive teachers (Kemmis, 1985; Freire, 2001; Dewey, 1933; Schön, 1983,1987; Zeichner, 1993; Alarcão, 2002; Pimenta, 1999; and Celani, 2001) and on curriculum as a freeing proposal which may include all participants of the teaching-learning process, promoting opportunities for questioning, reflection and awareness (Beyer & Apple, 1998; and Freire, 1970). The methodological approach chosen was the hermeneuticphenomenological one (van Manen, 1990). The research context was a community university in the countryside of São Paulo, in which the participants took Language. Data were collected from 2004 to 2006, deriving from activities developed in the classes of the teacher-researcher, which aimed at observing the education process of English teachers. The interpretation of the participants texts reveal that the phenomenon on focus was comprised by three major themes: Reflections about the English language and the development during their graduation course; Inter-relations of the developing teachers with the target language, professors, graduation classmates, and with their own development; and Confrontation of expectations in the linguistic and professional fields, considering disruptions and continuities. The phenomenon interpretation, grounded on the identified themes, allowed a new view of the English teachers education in a Language course, opening paths for questioning and changes